Pengaruh Perilaku Phubbing terhadap Kualitas Persahabatan pada Mahasiswa di Kota Makassar - Muh. Alif Ulil Absar Syukur; Sitti Murdiana (Universitas Kristen Maranatha, 2024)
The use of smartphones has adverse effects such as the emergence of the behavior of ignoring face-to-face conversations with other people due to excessive attention on smartphones, known as phubbing. The emergence of this behavior is assumed to affect the quality of interpersonal relationships, especially the quality of friendships among students. This study aims to determine the effect of phubbing behavior on the quality of friendship among students in Makassar. The data were obtained from 503 students and analyzed with simple linear regression analysis. The results showed that there is no significant negative effect of phubbing behavior on the quality of friendship among students in Makassar (p = 0.460). Another factor that might contribute to the low influence of phubbing behavior on friendship quality is the emergence of personal and observed behavior. This study is expected to increase students' awareness on phubbing and the impact of this behavior.